Late Godard and the possibilities of cinema / Daniel Morgan - Morgan, Daniel
With Late Godard and the Possibilities of Cinema, Daniel Morgan makes a significant contribution to scholarship on Jean-Luc Godard, especially his films and videos since the late 1980s, some of the most notoriously difficult works in contemporary cinema. Through detailed analyses of extended sequences, technical innovations, and formal experiments, Morgan provides an original interpretation of a series of several internally related films-Soigne ta droite (Keep Your Right Up, 1987), Nouvelle vague (New Wave, 1990), and Allemagne 90 neuf zéro (Germany 90 Nine Zero, 19.